2006
DOI: 10.1111/j.1365-313x.2006.02743.x
|View full text |Cite
|
Sign up to set email alerts
|

Altering glucosinolate profiles modulates disease resistance in plants

Abstract: SummaryPlant diseases are major contributing factors for crop loss in agriculture. Here, we show that Arabidopsis plants with high levels of novel glucosinolates (GSs) as a result of the introduction of single CYP79 genes exhibit altered disease resistance. Arabidopsis expressing CYP79D2 from cassava accumulated aliphatic isopropyl and methylpropyl GS, and showed enhanced resistance against the bacterial soft-rot pathogen Erwinia carotovora, whereas Arabidopsis expressing the sorghum CYP79A1 or over-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
153
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 47 publications
4
153
0
2
Order By: Relevance
“…Differential effects on microbial populations that we observed could result from variable direct susceptibility of populations towards antimicrobial properties of hydrolysis products of glucosinolates (Smith and Kirkegaard, 2002;Kliebenstein et al, 2005;Brader et al, 2006). Beside their antimicrobial effect, glucosinolates and their hydrolysis products could also stimulate microbial growth.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Differential effects on microbial populations that we observed could result from variable direct susceptibility of populations towards antimicrobial properties of hydrolysis products of glucosinolates (Smith and Kirkegaard, 2002;Kliebenstein et al, 2005;Brader et al, 2006). Beside their antimicrobial effect, glucosinolates and their hydrolysis products could also stimulate microbial growth.…”
Section: Discussionmentioning
confidence: 84%
“…Kristensen et al (2005) showed that insertion of CYP79A1 gene and accumulation of the novel glucosinolate had only marginal inadvertent effects on the plant transcriptome and metabolome compared with wild type. However, Brader et al (2006) showed that the accumulation of the novel glucosinolate could reduce the induction of jasmonate-mediated pathway but led to increased levels of salicylic acid. These plant defense pathways could modify the soil bacterial community structure (Kniskern et al, 2007;Hein et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These compounds and their breakdown products, for example, isothiocyanates, protect plants against herbivores and pathogens (Giamoustaris and Mithen, 1995;Mari et al, 1996;Manici et al, 2000;Reymond et al, 2004;Chung et al, 2005;Mewis et al, 2005;Brader et al, 2006) and are known to serve as human anticancer agents (Talalay and Fahey, 2001;Traw et al, 2003;Hayes et al, 2008). After Met-derived glucosinoates, indolic and benzyl glucosinolates are the most abundant glucosinolates in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…4-Methylsulphinylbutyl isothiocyanate was found to inhibit a wide range of fungi and bacteria (Tierens et al, 2001). Increased accumulation of aromatic GSs was shown to stimulate salicylic acid (SA)-mediated defenses, while suppressing jasmonic acid (JA)-dependent defenses (Brader et al, 2006). On the other hand, the GS metabolism was tightly related to some physiological processes under abiotic stresses, such as salinity, drought, heat, light, and nutrient deprivation (del Carmen Martínez-Ballesta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Upon tissue damage occurring, GSs are hydrolyzed into bioactive isothiocyanates, thiocyanates, or nitriles by the action of myrosinase (Ratzka et al, 2002;Borgen et al, 2010). These GS hydrolysis products are toxic to fungi, bacterial pathogens, or herbivores (Agrawal and Kurashige, 2003;Wittstock et al, 2003;Brader et al, 2006;Burow et al, 2006;Mumm et al, 2008;Redovniković et al, 2008).…”
Section: Introductionmentioning
confidence: 99%